New Zealand's Residential Price Dynamics: Do capability to consume and government policies matter? - Liew, Venus Khim Sen; Chong, Fennee (ECONOMICS BULLETIN, 2020)
The objectives of this paper are to provide empirical evidences on whether i) government policies represented by mortgage rate and loan-to-value ratio are associated with the dynamics of the New Zealand Residential Price Index, ii) macroeconomic factors such as house price to income ratio and inflation rate that proxy capability to consume, as well as population growth rate are the driving forces of housing market dynamics of the country. After testing a battery of statistical assumptions, this study adopts the Autoregressive Distributed Lag (ARDL) cointegration method to examine data from Quarter 1, 2009 to Quarter 2, 2019 for the short and long-run relationships among the variables. Findings show that mortgage rate, loan-to-value ratio, and inflation rate have negative long-run relationship with Residential Price Index. On the other hand, population growth rate and house price to income ratio are shown to have positive long-run impact on housing price. Results obtained from Error Correction Model reveal that whenever there is a short-run shock in the residential price dynamics, the Residential Price Index will take about three quarters to fully restore back to its long-run equilibrium. Additionally, mortgage rate, population growth rate, loan-to-value ratio and house price to income ratio are found to significantly Granger-cause New Zealand's residential price dynamics during the study period.